Alat Ukur Konstanta Waktu Resistor Kapasitor Berbasis Mikrokontroler - Febrian, Andi Wahyu; Jabbar, A. Abd.; Jasmawati, Jasmawati (Jurnal Mosfet, 2024)
Currently, the measurement of time constants in Resistor-Capacitor circuits still uses manual calculations, necessitating the development of measurement technology from analog to digital. This research aims to design and develop a digital-based time constant measurement tool for Resistor-Capacitor circuits. The research method uses a quantitative approach based on research and development with the implementation of an Arduino Nano microcontroller and Liquid Crystal Display. Testing was conducted on five capacitor variations with a fixed 100kΩ resistor in charging and discharging modes. Each test was performed five times to validate the consistency of results. The research results show that the developed measurement tool has a highest average error rate of 4.3%, well below the 10% tolerance limit. Comparative analysis with a standard multimeter shows good measurement consistency. This measurement tool can be implemented for digital measurement and analysis of Resistor-Capacitor circuits with a reliable level of accuracy.